Sexual freedom of personality (Journal of actual problems of jurisprudence, 2019)
Criminal law fight against criminal encroachment against sexual inviolabilitysexual freedom of the individual, ensuring the rights and legitimate interests of citizens in the field of sexualrelationship is one of the urgent tasks facing the bodies of investigation and inquiry.